Analysis of the Effect of Service Quality Dimensions on Customer Loyalty through Perceived Value, Image, Consumption Emotion and Customer Satisfaction on Shangri-La Hotel Customers in Surabaya: English - Setia, Laurentius Calvin; Ronald, Ronald; Amelia, Amelia (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
The growth of the hospitality industry in Indonesia shows a significant number. In this case requires the company to be able to meet customer needs and adjust customer desires in the overnight process so that the company must be able to detect what the needs and desires of its customers are. Therefore, the presence of Shangri-La Hotel Surabaya is very influential in the development of the hotel industry, especially in Surabaya. This study aims to analyze the effect of Service Quality dimensions on Customer Loyalty through Perceived Value, Image, Consumption Emotion and Customer Satisfaction to the Shangri-La hotel customers in Surabaya. The sample used in this study is 250 respondents. For processing and analyzing data in this study, namely by using Amos version 22.0 as software for data processing. This study has 12 hypotheses and all of them have significant results.